Proyecto de factibilidad para la creación de una empresa de producción de tilapia, en la ciudad de Zamora, provincia de Zamora Chinchipe, para el año 2016 - Gaona Reyes, Darwin José (2017)
The present work was carried out in the city of Zamora, aiming the study of the feasibility for the creation of a micro-enterprise of tilapia fish production. To achieve the development of the research was used different research methods and data collection techniques that were used to present the results of the project. For the market survey, surveys were applied to the families of the city of Zamora 364 surveys, which represented 7,077 families. The technique used was the survey and was applied through a questionnaire that served to obtain information on the supply and demand of the product, the same that corresponds to the market study which determines the existing demand for this product, the existing potential demand is Of 82.45%, the real demand is 94.73%, the effective demand is 94.93% and per capita consumption is 36 pounds per year for each family. As for the offer of this service, according to the research carried out there are only 3 companies dedicated to the production of Tilapia. In the technical study, the optimum size of the present project was established, the installed capacity determines the use of the premises ready for the lease of the operation of the company which consists of 5 large and a small fish that will serve to classify them . In addition, it is anticipated the location of the company which would be of macro form in the Province of Zamora Chinchipe, City of Zamora and of micro form in the Troncal Amazon Av. As for organizational structure requires the participation of 5 people, 3 of them hired full time and the other 2 with professional services or temporarily. Therefore, the company is constituted as "Unipersonal" and the respective procedures for operating permits are drawn up, beginning with obtaining the RUC in the Internal Revenue Service. In the Economic and Financial study the total Investment of USD $ 32,084.88 United States of America; Which will be financed 62.60% with internal sources and 37.40% with a loan to Ban Ecuador. In the Statement of Income, sales revenue is USD $ 67,500.00 United States of America, less the total cost of USD $ 42,325.71 United States of America; Gives a gross profit of USD $ 25,174.29 from the United States of America, which is deducted 15% of utility for workers, 22% of income tax and 10% of Legal Reserve obtaining a net profit Of USD $ 15,021.50 of the United States of America in the first year of operation of the company. For the calculation of the Break-even point in terms of sales revenue for the first year, it is USD $ 20,449.01 from the United States of America, based on installed capacity, a percentage of 30.37% where the project represents neither profit nor lost. In the Financial Assessment the main criteria determined that the net present value is positive with USD $ 89,804.22 from the United States of America. If it is convenient to accept the project, on the other hand, the internal rate of return is 27.46% which compared to the rate of opportunity cost of capital of 11.20% is higher, so the project is also acceptable. As for the period of capital recovery in this project is 1 year, 10 months and 8 days, RBC Benefit-Cost Ratio is USD $ 1.61 dollars from the United States of America and this indicates to us that For every dollar invested you will get USD $ 0.61 cents from the United States of America yield; And based on the sensitivity analysis shows that the project can withstand an increase of up to 10.00% in costs and a decrease in revenues of 10.00%. Consequently, with the results obtained and associated with the rest of the study, it is demonstrated the feasibility of the implementation of the proposed project.